Sistem Utang Piutang Pupuk Dibayar Gabah di Jember Perspektif Fiqih Muamalah dan Hukum Positif - Siti Muhlisah (Rechtenstudent, 2020)
Discussing about debt and credit is not foreign to everyone's ears. Accounts receivable is an agreement between one party and another with the agreed object and will be returned within a certain time as agreed. Debt and credit is a form of muamalah which is ta'awun (please help). The fact is that many debts and receivables are not following sharia and law in Indonesia. This study aims to determine and analyze how the practice of fertilizer receivables is paid with grain from the perspective of Fiqh Muamalah and Positive Law. The research method used is descriptive qualitative. The results of this study found that according to Fiqih Muamalah, the fertilizer receivable payable system is paid with grain that the transaction is allowed, but every addition in fertilizer receivables is paid with grain required by the creditor is usury. The practice of the fertilizer debt system being paid with grain also contradicts the principles of the contract, one of which is the divine principle, the principle of justice, and the principle of writing. In the Positive Law, the fertilizer accounts payable system is paid with the grain if it refers to the Supreme Court decision dated December 4, 1975, No. 804 K / Sip / 1973 principal debt plus 6% interest, because 6% interest is the usual interest at the time the agreement was held. And must be stipulated in writing. Meanwhile, the interest in the debt and credit is more than 70%.